Kajian Level Kinerja Struktur Apartemen 25 Lantai terhadap Beban Gempa dengan Analisis Pushover pada Sumbu Kuat - Gita Zakiah Putri; Edra Gradi Wartono (Jurnal Karajata Engineering, 2025)
High-rise projects like 25-storey apartment buildings often face construction challenges due to dense reinforcement, particularly in shear walls. Spatial constraints may prevent full rebar installation, as seen in a studied project in Jakarta, leading to minor reinforcement reductions. Although seemingly insignificant, such reductions can affect ductility and seismic performance. The site lies in Seismic Design Category D per SNI 1726:2019, requiring special seismic detailing and ensuring structures meet at least Damage Control (DC) performance under Maximum Considered Earthquake (MCE) conditions (2% probability in 50 years). The building uses a dual system—moment-resisting frames and shear walls—with a ductility factor of R=7R = 7R=7, following ATC-40 guidelines. Pushover analysis showed a maximum base shear of 3063.76 kN at 1298.59 mm roof displacement (step 18), while the performance point was reached at 619.45 mm displacement and 2250.89 kN base shear. Plastic hinges formed first in beams at step 7 and progressed until step 18. The building satisfies the DC performance level, indicating it can endure MCE-level earthquakes with low life-safety risk. Estimated repair costs at this level are around 35% of the structural value, confirming acceptable structural performance and safety for occupancy during major seismic events.